1996
DOI: 10.1111/j.1476-5381.1996.tb15728.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytochrome P450 inhibitors on potassium currents and mechanical activity in rat portal vein

Abstract: 1 The effects of the cytochrome P450 inhibitors, proadifen, clotrimazole and 17-octadecynoic acid (17-ODYA) on K-currents in freshly-isolated single cells derived from rat portal vein and on mechanical activity in whole veins were studied. 2 When cells were stepped from -90 mV to a series of test potentials (from -80 to +50 mV), a delayed rectifier current (IKV) and an A-type current (IK(A)) could be identified. Proadifen (10 yM), clotrimazole (30 gM) and 17-ODYA (5 uM) each inhibited IKV but had little effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…96 Additionally, in numerous vascular preparations from various species, EETs evoke no or minor relaxations and/or hyperpolarization, indicating that in these arteries non-NO-non-PGI 2 -mediated responses are unlikely to rely on this metabolite of arachidonic acid. 7 The lack of selectivity of the available tools 97,98 has made it difficult to determine whether the activation of the endothelial potassium channels IK Ca and/or SK Ca or the release of EETs underlies non-NO-non-PGI 2 -mediated responses. For instance, clotrimazole, a reference inhibitor of cytochrome P450 epoxygenases, also blocks IK Ca .…”
Section: Other Identified Endothelium-derived Hyperpolarizing Substancesmentioning
confidence: 99%
“…96 Additionally, in numerous vascular preparations from various species, EETs evoke no or minor relaxations and/or hyperpolarization, indicating that in these arteries non-NO-non-PGI 2 -mediated responses are unlikely to rely on this metabolite of arachidonic acid. 7 The lack of selectivity of the available tools 97,98 has made it difficult to determine whether the activation of the endothelial potassium channels IK Ca and/or SK Ca or the release of EETs underlies non-NO-non-PGI 2 -mediated responses. For instance, clotrimazole, a reference inhibitor of cytochrome P450 epoxygenases, also blocks IK Ca .…”
Section: Other Identified Endothelium-derived Hyperpolarizing Substancesmentioning
confidence: 99%
“…The differences among the studies in human subcutaneous arteries may result from different CYP450 inhibitors used, which have their own limitations. For example, it has been shown that nonspecific inhibitors of CYP450 such as micanazole and other imidazoles may also block K ϩ channels (14) or impair the agonist-induced increase in intracellular Ca 2ϩ in endothelial cells (20). This could prevent EDHF-mediated effects on smooth muscle rather than affecting the synthesis/release of EDHF itself.…”
Section: Role For Aa Metabolites In Edhf-mediated Responsesmentioning
confidence: 99%
“…Indeed, the production of EDHF from coronary arteries can be inhibited by the suicide P450 inhibitor, 17-octadecynoic acid in bioassay experiments [29, 31]. It is however likely that more than one EDHF exists since the hyperpolarizing factor released from the rabbit aorta [32], guinea pig carotid [33] and rat mesenteric and hepatic arteries [34, 35] or the rat portal vein [36] exhibits very different pharmacological characteristics to that of the ‘coronary EDHF’. Recently, a specific cannabinoid receptor (CB1) antagonist has been shown to attenuate EDHF-induced relaxation of isolated rat mesenteric vessels while anandamide (arachidonoylethanolamide), an endogenous ligand for central cannabinoid receptors [37, 38], elicited EDHF-like relaxations [39].…”
Section: Endothelium-derived Autacoidsmentioning
confidence: 99%